2017
DOI: 10.1038/s41565-017-0019-5
|View full text |Cite
|
Sign up to set email alerts
|

Direct-current triboelectricity generation by a sliding Schottky nanocontact on MoS2 multilayers

Abstract: The direct conversion of mechanical energy into electricity by nanomaterial-based devices offers potential for green energy harvesting . A conventional triboelectric nanogenerator converts frictional energy into electricity by producing alternating current (a.c.) triboelectricity. However, this approach is limited by low current density and the need for rectification . Here, we show that continuous direct-current (d.c.) with a maximum density of 10 A m can be directly generated by a sliding Schottky nanocontac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
240
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 256 publications
(256 citation statements)
references
References 24 publications
8
240
1
Order By: Relevance
“…It is necessary to check the consistency of semiconducting properties after joining metal nanoparticles. Due to the rather challenging measurement of electric current from nanoscale samples, conductive‐atomic force microscope (C‐AFM) determinations were employed to measure the conductivity . As illustrated in Figure a, the C‐AFM method measures a total electrical resistance of the system, with the contact resistance Ni–Au–MoS 2 included.…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary to check the consistency of semiconducting properties after joining metal nanoparticles. Due to the rather challenging measurement of electric current from nanoscale samples, conductive‐atomic force microscope (C‐AFM) determinations were employed to measure the conductivity . As illustrated in Figure a, the C‐AFM method measures a total electrical resistance of the system, with the contact resistance Ni–Au–MoS 2 included.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] Traditional triboelectric nanogenerators (TENGs) may generate high voltage but with extremely low AC current ( J ≈ 0.01-0.1 A m −2 ) density. [1][2][3] Traditional triboelectric nanogenerators (TENGs) may generate high voltage but with extremely low AC current ( J ≈ 0.01-0.1 A m −2 ) density.…”
mentioning
confidence: 99%
“…[1] The performance of TENGs is optimal only at high frequency due to the dielectric displacement current mechanism, while the environmental mechanical sources usually have frequencies lower than 10 Hz. [3,[5][6][7][8][9][10] The tribo-tunneling transport tip-enhanced current generation, as reported by Liu et al [3,6] using conductive-atomic force microscope (C-AFM), show that the tribo-tunneling current density ( J) output can be boosted by the nano-sized contact (tip radius R ≈ 30 nm) up to 10 6 A m −2 due to the enhanced electronic excitation and strong localized electric field E. It has been reported that a micro-tip (tip radius R ≈ 30 µm) sliding system produces a current density of 35 A m −2 while larger tip radius (R ≈ 100-300 µm) yields a current density of 10 A m −2 in the test probe sliding system. [3,[5][6][7][8][9][10] The tribo-tunneling transport tip-enhanced current generation, as reported by Liu et al [3,6] using conductive-atomic force microscope (C-AFM), show that the tribo-tunneling current density ( J) output can be boosted by the nano-sized contact (tip radius R ≈ 30 nm) up to 10 6 A m −2 due to the enhanced electronic excitation and strong localized electric field E. It has been reported that a micro-tip (tip radius R ≈ 30 µm) sliding system produces a current density of 35 A m −2 while larger tip radius (R ≈ 100-300 µm) yields a current density of 10 A m −2 in the test probe sliding system.…”
mentioning
confidence: 99%
“…Among the three types of SLNGs, the capacitorbased is synthetically most competitive in the senses of performance, fabrication and maintaining. These results can guide designs and accelerate fabrications of SLNGs toward real applications.With the rapid developments of nanotechnology and microfabrication technology, ceaselessly miniaturized sensors and devices are emerging in vast numbers of applications in internet of things, sensor networks, big data, personal health systems, artificial intelligence, et al [1][2][3][4][5] . Until now, these sensors and devices have been mostly powered by batteries and external chargers, which limits their applications 12,13 particularly in needs for independent, sustainable, maintain-free operations of implantable biosensors, remote and mobile environmental sensors, nano/micro-scale robots or other electromechanical systems, portable/wearable person electronics, et al [13][14][15][16] .…”
mentioning
confidence: 99%
“…However, low electric current densities and short product lifespans of current nanogenerators have blocked real applications of nanogenerators explored so far 3,6,18 .…”
mentioning
confidence: 99%